Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Belanja Modal di Kabupaten dan Kota Provinsi Jambi Tahun 2010-2018 - Pantun Bukit; M Alhudhori (Universitas Batanghari Jambi, 2020)
The aims of this research are to know: 1) The effect of Original Local Goverment Revenues to the Capital Expenditures in Special Region of Jambi Province. 2) The effect of General Allocation Funds to the Capital Expenditures in Special Region of Jambi Province. 3) The effect of Special Allocation Funds to the Capital Expenditures in Special Region of Jambi Province. 4) The effect of Original Local Goverment Revenues, General Allocation Funds and Special Allocation Funds simultaneously to the Capital Expenditures in Special Region of Jambi Province. The population in this research is regency and municipality in Special Region of Jambi Province. Data used comes from APBD Realization Report years 2010-2018. The technique of collecting data used documentation method. The test of prerequisite analysis used classical assumption test, those are normality, multicolinearity, heteroscedasticity and autocorrelation. The hypothesis test in this research used simple and multiple linear regression analysis. The results show that local revenue, general allocation funds, and profit sharing funds simultaneously affect capital expenditure where together these three variables have a 48% effect on capital expenditure, while partially local revenue has a positive and significant effect on spending. capital with a coefficient of 0.370 for general allocation funds also has a positive and significant effect on capital spending with a regression coefficient of 0.211 and profit-sharing funds partially also have a positive and significant effect on capital spending with a regression coefficient of 0.514.